Synthesis of hydroxyapatite nanorods from abalone shells via hydrothermal solid-state conversion. (15th December 2015) - Chen, Jingdi; Wen, Zhenliang; Zhong, Shengnan; Wang, Zihao; Wu, Jiulin; Zhang, Qiqing
Abstract: Hydroxyapatite (HAP) has been widely applied as a biomaterial for repairing or substituting human hard tissues. In this paper, HAP nanorods were successfully produced from abalone shell powders via hydrothermal solid-state conversion without surfactants or complex agents. The field emission scanning electron microscopy (FESEM) showed that the produced HAP exhibited the typical rod-like structure. Based on the X-ray diffraction (XRD) and thermal analysis (thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC)), these samples contain a small amount of aragonite and calcite crystals, and their content gradually decreases by prolonging the hydrothermal time. However, this decrease only slightly changes for the longer times. The Fourier transform infrared spectroscopy (FTIR) revealed that organic matter was detected in the samples without adding surfactants or complex agents. This study provides a solution to the resource waste and environmental pollution caused by abandoned abalone shells, and we also synthesized HAP for potential bone repair materials. Graphical abstract: Highlights: Hydroxyapatite was synthesized from abandoned abalone shell. The morphology of the hydroxyapatite is a typical rod-like structure. A mechanism for the hydroxyapatite synthesis was proposed from aragonite and calcite.